The THE ROLE OF PARENTAL PATTERNS IN SUPERVISING LEARNING AT HOME FOR VULNERABLE STUDENTS IN GRADES 1 TO 3 OF MANTINGAN 3 ELEMENTARY SCHOOL: PERAN POLA PERAN ORANG TUA DALAM MENGAWASI PEMBELAJARAN DI RUMAH BAGI SISWA RENTAN KELAS 1 SAMPAI 3 SEKOLAH DASAR MANTINGAN 3 - Ilham Wisnu Murti; Sukartono (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the role of parental parenting patterns in supervising home-based learning for vulnerable students in Grades 1–3 at SDN Mantingan 3. A descriptive qualitative approach with a case study design was employed to gain in-depth understanding of social phenomena and the meanings behind parents’ guidance behaviors. Primary data were collected through observations and in-depth interviews with parents, while secondary data were obtained from relevant literature. Data analysis was conducted interactively using Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The results indicate that democratic parenting is the most effective style for supporting home learning, characterized by warm communication, clear guidance, opportunities for children to ask questions and experiment, and consistent emotional support. This approach enhances intrinsic motivation, self-confidence, curiosity, learning independence, time management, task completion, and self-evaluation. Supporting factors include parental commitment, a conducive learning environment, emotional closeness, and active communication with teachers, while main obstacles are limited parental time, low academic competence, socioeconomic constraints, and environmental distractions.